KARAKTER DAN NILAI MORAL DALAM FILM THE PATRIOT KARYA ROLAND EMMERICH - Okki Hafnan (Universitas Indraprasta PGRI, 2021)
Abstract: The paper aims to analyze the problem as follows: 1) how the characters in the film and 2) how the moral values contained in Roland Emmerich’s film The Patriot. The research method used is qualitative, with primary data sources taken from the film and secondary literature outside of the film. The data collection technique used is the documentation of Creswell. Documentation is a method used in scientific research to collect data using documents or lists of evidence and data analysis techniques used based on the Moleong theory. The character theory used is Russell’s theory, while for moral values in the film, the writer uses Setyosih’s theory. The results showed that; as; 1) the characters are divided into three, namely dominating characters are the protagonist (48%), antagonist (28%), and foil (24%). 2) moral values are divided into 6, namely; tolerance (13%), fairness (9.09%), trust (18.18%), kindness (32.81%), honesty (4.54%), and responsibility (22.72%). This research is good for school and public education.Keywords: characters, moral values, movie, content analysis